Analisis Penyebaran Hoaks COVID-19 di Indonesia - Endang Indartuti; Indah Murti; Kusnan Kusnan (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
In Indonesia, social media is considered one of the primary channels for the massive spread of hoaxes related to the COVID-19 pandemic. The spread of hoaxes through social media is difficult to control due to the rapid advancement of internet-based information technology and the low level of digital literacy among the public. This study aims to analyze the dissemination of hoaxes and the keywords frequently associated with COVID-19 hoaxes in Indonesia from 2020 to 2022. Employing a descriptive qualitative research approach, this study uses non-participant observation on the website turnbackhoax.id as the data collection method and applies an interactive model for data analysis. The findings reveal that COVID-19 hoaxes in Indonesia are predominantly classified into misleading content, false context, and fabricated content, with fabricated content being identified as the most dangerous type.